Single Amino Acid Substitution in the DNA Repairing Gene Radiation-Sensitive 4 Contributes to Ultraviolet Tolerance of a Plant Pathogen - Wang, Yan-Ping; Yang, Li-Na; Feng, Yuan-Yuan; Liu, Songqing; Zhan, Jiasui (Frontiers in Microbiology, 2022)
To successfully survive and reproduce, all species constantly modify the structure and expression of their genomes to cope with changing environmental conditions including ultraviolet (UV) radiation. Thus, knowledge of species adaptation to environmental changes is a central theme of evolutionary studies which could have important implication for disease management and social-ecological sustainability in the future but is generally insufficient. Here, we investigated the evolution of UV adaptation in organisms by population genetic analysis of sequence structure, physiochemistry, transcription, and fitness variation in the radiation-sensitive 4 (RAD4) gene of the Irish potato famine pathogen Phytophthora infestans sampled from various altitudes. We found that RAD4 is a key gene determining the resistance of the pathogen to UV stress as indicated by strong phenotype-genotype-geography associations and upregulated transcription after UV exposure. We also found conserved evolution in the RAD4 gene. Only five nucleotide haplotypes corresponding to three protein isoforms generated by point mutations were detected in the 140 sequences analyzed and the mutations were constrained to the N-terminal domain of the protein. Physiochemical changes associated with non-synonymous mutations generate severe fitness penalty to mutants, which are purged out by natural selection, leading to the conserved evolution observed in the gene.